Agricultural production and south Asian history / edited by David Ludden - Ludden, David (ed.) (New Delhi, 2006)
Contemporary trends have produced a distinctly new setting for the second edition of Agricultural Production and Indian History, which now merits a new title, Agricultural Production and South Asian History, to highlight India's South Asian context and the progressive merger of agrarian history, and development stud ies. We can now see the twentieth century more clearly as history. The 1980s now appear as a watershed decade, dividing our present day from earlier times.' The age of national indepen dence is now firmly ensconced in the history of modernity, where liberalization and globalization appear as recent trends propelled by market forces, interests, ideas, technologies, and conflicts that arrived in the nineteenth century, which we can embrace loosely but usefully by the term 'capitalism."2 Until the 1980s, national governments endeavoured to lead economic de velopment so as to fortify independence and sovereignty by guiding, constraining, and promoting capitalism in the national interest. Since then, however, most politicians have come to believe and most students have learnt in school that nations can only develop successfully by letting markets lead the way and joining the world of free market competition.
Keywords: Agricultural production